Antihyperlipidemic effect of Cyclocarya paliurus (Batal.) Iljinskaja extract and inhibition of apolipoprotein B48 overproduction in hyperlipidemic mice. (26th May 2015) - Ma, Yonglan; Jiang, Cuihua; Yao, Nan; Li, Yue; Wang, Qingqing; Fang, Shengzuo; Shang, Xulan; Zhao, Ming; Che, Chuntao; Ni, Yicheng; Zhang, Jian; Yin, Zhiqi
Abstract: Ethnopharmacological relevance: Cyclocarya paliurus (CP) Batal., the sole species in its genus, is a native plant to China. As a traditional Chinese folk medicine, the tree leaves have been widely used for the treatment of metabolic disorders, including hyperlipidemia, obesity, diabetes and hypertension. Aim of the study: The study aimed to evaluate the antihyperlipidemic effect of CP ethanol extract, as well as its inhibitory activity on apolipoproteinB48 (apoB48), in normal and hyperlipidemic mice. Materials and methods: The antihyperlipidemic effect of CP was evaluated in hyperlipidemic mice induced by high-fat diet for 4 weeks. CP ethanol extract (0.37, 0.75 and 1.5 g/kg/day) was orally administrated once daily. Lipids and antioxidant profiles, including total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), malondialdehyde (MDA), superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), together with the indices of hepatic and renal functions were examined. RT-qPCR and western blotting were used to analysis the expression levels of tumor necrosis factor (TNF-α), total- and triglyceride-rich apoB48 (TRL-apoB48), as well as the phosphorylation of the mitogen-activatein kinase (MAPK). Results: CP as well as simvastatin remarkably lowered the levels of TC, TG, LDL-C and MDA, and at the same time, elevated the HDL-C, SOD and GSH-Px in high-fat diet mice. It also decreased the serum concentration of total- and TRL-apoB48 in the fasting state. CP inhibited TNF-α expression and phosphorylation level of MAPK. Furthermore, the HE staining of liver and kidney, together with hepatic and renal function analysis showed hepato- and renoprotective activities of CP. Conclusions: These results suggested that CP possesses beneficial potentials for use in treating hyperlipidemia and the underlying lipid-lowering mechanism might associate with a down-regulation of the intestinal-associated lipoprotein apoB48, which may provide evidence about its practical application for treating hyperlipidemia and its complications. Graphical abstract: